Synthesis of Some Heterocyclic Schiff Base and Azetidinone Compounds and Their Antibacterial Activity - D. Naik, Bhanvesh; Desai, K.R. (Asian Journal of Chemistry, 2016)
As a target to synthesize various Schiff base and azetidinone derivatives, 2-amino-4-(coumarinyl-3)-thiazole has been prepared by the reactions of 3-bromo acetyl coumarin with thiourea. 3-Bromo acetyl coumarin was prepared from 3-acetyl coumarin. The resulting compound 2-amino-4-(coumarinyl-3)-thiazole was treated with different aldehydes to give the Schiff base which on further reaction with chloro acetyl chloride gave the titled compounds. The structures of the compounds have been confirmed by elemental analysis and spectral analysis. The antibacterial activity of the compounds has also been screened.